Sirtuin 7 Promotes Mesenchymal to Epithelial Transition by β-Catenin Redistribution and Stabilization - Kiran, Shashi; Kiran, Manjari; Ramakrishna, Gayatri (Frontiers in Oncology, 2020)
SIRT7 belongs to the family of “NAD+ dependent deacetylases” called Sirtuins .In the present work we report a novel role of SIRT7 in regulating cellular polarity. SIRT7 overexpression in immortalized mouse fibroblasts (NIH3T3) induced epithelial transition. This transition was accompanied by typical N- to E- cadherin transition, stabilization of β-catenin and downregulation of transcription factors responsible for maintenance of mesenchymal phenotype (Snail, Slug and Zeb1). Interestingly a subpopulation of cells overexpressing SIRT7 exhibited an intermediate stage between mesenchymal and epithelial characters. Transformed epithelial cells showed a loss of heterochromatisation as evidenced by loss of HP1α and H3K9 dimethylation staining. In conclusion, we report a role of SIRT7 in mesenchymal cells , which may have implications in health and disease.